2021
DOI: 10.3390/pharmaceutics13070940
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Nanotechnology-Facilitated Bacteria-Based Drug and Gene Delivery Systems for Cancer Treatment

Abstract: Cancer is one of the most devastating and ubiquitous human diseases. Conventional therapies like chemotherapy and radiotherapy are the most widely used cancer treatments. Despite the notable therapeutic improvements that these measures achieve, disappointing therapeutic outcome and cancer reoccurrence commonly following these therapies demonstrate the need for better alternatives. Among them, bacterial therapy has proven to be effective in its intrinsic cancer targeting ability and various therapeutic mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 94 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…When IBU-SNE-FM contacts body fluids, various components of SNEDDS will self-assemble into lamellar liquid crystals due to hydrogen bonding and hydrophobic forces, and further spontaneously form nanoemulsions (NE), which can facilitate the transdermal penetration of the drug ( Figure 9 ). In vitro permeation experiments of rat skin showed that the drug permeability coefficient of IBU-SNE-FM was 1.79 and 1.67 times higher than that of IBU’s phosphate buffer, and the IBM nanofibers (IBU was directly dissolved in PLLA ethanol solution for electrospinning) after 4 h. In the acute inflammation model in rats induced with CFA, the IBU-SNE-FM group significantly reduced the inflammation infiltration and the swelling thickness of rat paws, which can effectively exert the anti-inflammatory effect (Xiang et al., 2019 ).…”
Section: Ra Transdermal Dosage Formmentioning
confidence: 99%
See 1 more Smart Citation
“…When IBU-SNE-FM contacts body fluids, various components of SNEDDS will self-assemble into lamellar liquid crystals due to hydrogen bonding and hydrophobic forces, and further spontaneously form nanoemulsions (NE), which can facilitate the transdermal penetration of the drug ( Figure 9 ). In vitro permeation experiments of rat skin showed that the drug permeability coefficient of IBU-SNE-FM was 1.79 and 1.67 times higher than that of IBU’s phosphate buffer, and the IBM nanofibers (IBU was directly dissolved in PLLA ethanol solution for electrospinning) after 4 h. In the acute inflammation model in rats induced with CFA, the IBU-SNE-FM group significantly reduced the inflammation infiltration and the swelling thickness of rat paws, which can effectively exert the anti-inflammatory effect (Xiang et al., 2019 ).…”
Section: Ra Transdermal Dosage Formmentioning
confidence: 99%
“… IBU-SNE-FM transdermal delivery process. Copyright 2019, American Chemical Society (Xiang et al., 2019 ). …”
Section: Ra Transdermal Dosage Formmentioning
confidence: 99%
“…Among them, nanomedicine has achieved tremendous progress in cancer management [12][13][14]. Nanoparticles can protect the cargo from degradation and facilitate their accumulation at tumor sites through passive diffusion or active targeting, optimizing the drug biodistribution [15][16][17][18][19]. Especially in the past few years, nanocarriers that can respond to biological cues in the tumor microenvironment (TME) attracted increasing attention [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the inherent tropism of bacteria for different types of tumors and their ability to overcome the vascular barrier means that they have potential for use in tumor-targeting delivery ( Wu et al, 2021 ). Furthermore, the cell surfaces of bacteria can be decorated with organic or inorganic materials, including various types of nanomaterial and therapeutic agents for cargo delivery ( Zhu C. et al, 2021 ; Ye et al, 2021 ; Jiménez-Jiménez et al, 2022 ). Additionally, bacterial derivatives—including outer membrane vesicles (OMVs), minicells, and bacterial protoplast-derived nanovesicles—have been shown to have great potential as safe and efficient drug carriers ( Ali et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%